Production of neutrophil extracellular traps (NETs) in response to Scedosporium apiospermum in a murine model of pulmonary infection. (December 2020) - Luna-Rodríguez, Carolina E.; González, Gloria M.; Montoya, Alexandra M.; Treviño-Rangel, Rogelio de J.; Sánchez-González, Alejandro
Abstract: Scedosporium apiospermum is an opportunistic emerging pathogen that can develop in both immunosuppressive and immunocompetent patients with pulmonary infections. Neutrophils are recognized as critical cells in the early response to a fungal infection through different mechanisms that eliminate or control the infection such as neutrophil extracellular traps (NETs). In this work, we investigate the presence of NETs in the lung tissue of immunocompetent mice infected with Scedosporium apiospermum . In the histopathological study the presence of filamentous basophilic material with hematoxylin-eosin and periodic acid Schiff stains suggestive of extracellular DNA was observed. We demonstrated the presence of NETs by immunofluorescence staining of extracellular DNA, myeloperoxidase, and elastase in lung tissue. Our results showed that on days 1 and 3 post-infection extracellular DNA, myeloperoxidase, and elastase correlate with areas of high concentration of cell infiltrates and fungal structures. The observation of fungal structures in the tissue decreased as did the presence of NETs by day 5 post-infection. We suggest that NETs release may play an important role in the early containment of Scedosporium apiospermum lung infection. Highlights: NETs release in Scedosporium apiospermum lung infection in immunocompetent mice. Fungal tissue presences decreased along with NETs by day 5 post-infection. NETs could contribute to the containment of fungi during the pulmonary infection.